A proteção da educação no direito internacional dos direitos humanos e a prestação privada deste direito: possibilidades de uma adequação dos vouchers educacionais aos standards de direitos humanos? - PEREIRA, Bianca Araujo de Oliveira (Universidade Federal do Pará, 2018)
The present work discusses the possibility of reconciling educational vouchers – a model of educational services provided by the economist Milton Friedman - with the standards for the right to education, based on the special reports on the right to education, made by former rapporteur Kinshore Sing. To analyze this possibility, it is first approached the origin of the United Nations and its relationship with the promotion of the access to education. Next, the strands of liberal thought are discussed, followed by the dialogue between the critics of philosophical liberalism; there is also the approach of Public Choice Theory, New Public Management and its critics. The work also uses the empirical approach, based on a review of the existing literature, in order to elucidate the positives and negatives effects on the use of educational vouchers, in order to be able to answer the proposed research question.